1997
DOI: 10.1152/jn.1997.78.3.1563
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation Modulates Current Amplitude and Kinetics of a Neuronal Voltage-Gated Potassium Channel

Abstract: The modulation of the Kv1.3 potassium channel by tyrosine phosphorylation was studied. Kv1.3 was expressed in human embryonic kidney (HEK 293) cells, and its activity was measured by cell-attached patch recording. The amplitude of the characteristic C-type inactivating Kv1.3 current is reduced by >95%, in all cells tested, when the channel is co-expressed with the constitutively active nonreceptor tyrosine kinase, v-Src. This v-Src-induced suppression of current is accompanied by a robust tyrosine phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
112
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 45 publications
0
112
0
Order By: Relevance
“…Without the assisting role of the amino terminus in CMD action, stabilization of opening does not occur, and P o is lowered by Src phosphorylation. Precedent for dual tyrosine phosphorylation of K ϩ channels involved in tyrosine kinase modulation comes from Kv1.3 channels, which are doubly phosphorylated by v-Src at a tyrosine in each terminus of the channel, for which a kinase-dead v-Src mutant has little effect (1,7). In that study, adapter proteins were shown to act as controllers of Src action either facilitating or blocking the signal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Without the assisting role of the amino terminus in CMD action, stabilization of opening does not occur, and P o is lowered by Src phosphorylation. Precedent for dual tyrosine phosphorylation of K ϩ channels involved in tyrosine kinase modulation comes from Kv1.3 channels, which are doubly phosphorylated by v-Src at a tyrosine in each terminus of the channel, for which a kinase-dead v-Src mutant has little effect (1,7). In that study, adapter proteins were shown to act as controllers of Src action either facilitating or blocking the signal.…”
Section: Discussionmentioning
confidence: 98%
“…These proteins often act via two mechanisms: by binding to substrate via Src homology (SH) 1 2 and SH3 domains and/or by phosphorylation of target tyrosines (24). For example, distinct effects of Src actions by these two mechanisms have been described for Kv1.4 and Kv1.5 K ϩ channels (6).…”
mentioning
confidence: 99%
“…Both receptor and cellular tyrosine kinases, have been shown to acutely suppress Kv1.3 current by direct tyrosine phosphorylation. [3][4][5][6][7][8] Moreover, tyrosine kinase-mediated suppression of Kv1.3 current can be further modulated by direct proteinprotein interactions by adaptor and scaffolding proteins such as postsynaptic density-95 (PSD-95), n-Shc or Grb10. 9,10 Kv1.3 is involved in a variety of functions and is expressed in both excitable and nonexcitable tissues including, but not limited to, the olfactory bulb, 11 white and brown adipose tissue, 12 skeletal muscle, 12 the hypothalamus, 13 T lymphocytes 14 and their mitochondria, 15 and brain microglia.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major functions of SFKs is to regulate the activity of voltage-gated ion channels (Cataldi et al, 1996;Fadool et al, 1997) and ionotropic neuro-transmitter receptors (Moss et al, 1995;Wan et al, 1997;Wang et al, 2004). Src was also found to be involved in synaptic transmission and plasticity as well as excitotoxicity since Src regulated NMDA receptor activity (Wang and Salter, 1994;Yu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%